Do nonlinear waves evolve in a universal manner in dusty and other plasma environments? - Bharuthram, R.; Singh, S.V.; Maharaj, S.K.; Moolla, S.; Lazarus, I.J.; Reddy, R.V.; Lakhina, G.S. (My University, 2014)
Using a fluid theory approach, this article provides a comparative study on the evolution of nonlinear waves in dusty plasmas, as well as other plasma environments, viz electron-ion, and electron-positron plasmas. Where applicable, relevance to satellite measurements is pointed out. A range of nonlinear waves from low frequency (ion acoustic and ion cyclotron waves), high frequency (electron acoustic and electron cyclotron waves) in electron-ion plasmas, ultra-low frequency (dust acoustic and dust cyclotron waves) in dusty plasmas and in electron-positron plasmas are discussed. Depending upon the plasma parameters, saw-tooth and bipolar structures are shown to evolve.
Keywords: Plasma environments; Nonlinear waves; Dusty plasmas